Occurrence of Human Enteric Adenoviruses in Fresh Tropical Seafood from Retail Markets and Landing Centers. Issue 8 (23rd July 2019) - Ghosh, Subal Kumar; Lekshmi, Manjusha; Das, Oishi; Kumar, Sanath; Nayak, Binaya Bhusan
Abstract : Abstract: Human adenoviruses (HAdVs) are the foodborne enteric pathogens transmitted by the consumption of contaminated shellfish. In this study, the occurrence of enteric adenoviruses in finfish and shellfish was investigated by virus concentration and polymerase chain reaction (PCR). Total plate count, total coliform, and fecal coliform levels were determined and correlated with the presence of adenovirus. Samples of fish, bivalve mollusks, crustaceans, and cephalopods were collected from supermarkets, landing centers, and retail fish markets of Mumbai, India for the study. Overall, the adenovirus DNA was detected in 21.27% of all the samples analyzed. The highest incidence was detected in clams (14.89%), followed by oysters, shrimps, and finfish (2.13% each). High prevalence of enteric adenovirus in filter‐feeding bivalves, such as clams and oysters, as well as in fish suggests persistent fecal contamination of coastal waters in the region of study. The occurrence of adenoviruses in samples showed a positive correlation with the bacteriological indicators of fecal contamination, suggesting that fecal indicator bacteria may be used to monitor the presence of adenoviruses in seafood. Practical Application: This research demonstrates the occurrence of human adenoviruse (HAdV) in fresh seafood and the utility of fecal coliforms as indicators of HAdV presence in seafood. The study emphasizes the need to identify HAdV in seafood as a human health hazard and implement measures to prevent sewage pollution of fish and shellfish harvesting areas in India.